FAKTOR YANG MEMPENGARUHI TINGKAT PEMAHAMAN MATEMATIKA SISWA TUNANETRA - Mahardiyanti, Taurinda; Darmo, Santi Yudhawati (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2017)
This research aims to know the factors that influence profound visual disability student’s understanding on mathematics at Glonggong subdistrict of Putra Idhata SLB Dolopo Madiun Regency. This research included in the descriptive qualitative research, collection of data in this study use techniques of observation, interview and documentation. While the data were analyzed interactively through data reduction, data presentation, and data verification, and to check the validity of the data is done by triangulation techniques and resources. Based on the results of the research, the factors affecting profound visual disability students in learning mathematics in SLB Putra Idhata Glonggong Madiun Regency Dolopo Sub can be distinguished into two factors, namely the intrinsic factor and extrinsic factors. the intrinsic factor that affect the level of student’s understanding in mathematics includes: a) profound visual disability  student's physical conditions); b) the intelligence of students; c) lack of stimulus and motivation; d) psychological factors of students before the study begins; and e) causes and time of occurrence of becoming profound visual disability. Whereas extrinsic factors that affect the level of student’s understanding in mathematics including: a) the condition of inadequate class; b) lack of media used by teachers in learning mathematics; c) existence of teachers; and d) material being taught.